An Investigation into the Effectiveness of Under Platform Exhaust Systems Based on Measurements from the Copenhagen Metro - S Ravn (The Australasian Institute of Mining and Metallurgy, 2011)
Under platform exhaust (UPE) systems are often designed into metro stations as a means of removing heat generated by trains as they come to a halt in the platform. These systems are designed to extract heat from the brakes and brake resistors directly at the source in order to capture as much heat as possible before it can enter the public areas of the station, or contribute to the temperature build-up in the tunnels. Due to space requirements for the associated duct and air handling units, the UPE plays a significant role in the geometric design of the platform and station as a whole.In recent years questions have arisen as to the effectiveness of UPE systems. However, very little data is available for designers to use when making important decisions on the station designs for new metro systems. This is important as significant savings could be achieved by omitting or re-designing these systems for new build stations; not only due to the capital costs of space provision for the duct itself but also due to the associated operation and maintenance cost of the UPE system.This paper will present recent measurements of the UPE system of the Copenhagen metro together with one-dimensional (1D) simulations, looking at typical dispersion of heat into the station plenum box and air exchange through draught relief shafts as the train enters the station in order to evaluate the effectiveness of the UPE system. The aim of this paper is to disseminate the results of measurements and analysis to increase awareness of the issue and to provide discussion relevant to designers in their evaluation of heat removal systems in new build station designs.